SPE International Heavy Oil Symposium 1995
DOI: 10.2118/30294-ms
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Naptha to Replace Steam in the SAGD Process

Abstract: World-wide experience indicates that thermal methods are the only effective methods for the in-situ recovery of heavy oils. Furthermore, the steady progress within horizontal well technology increases the applicability of thermal methods in con)unction with horizontal wells. The steam"assisted gravity drall1age (SAGD) process is the prominent example of the synergism of horizontal wells with steam injection.The major portion of the dollar per barrel operational cost for steam injection is currently attributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…They concluded that smaller solvent slugs are more effective in bitumen recovery and that there is an optimum combination of solvent and steam slug size. These earlier efforts to improve steamflood process with the use of solvent led some investigators to suggest the combination of thermal effect and solvent dilution in SAGD (9,10) . Gupta et al (11) at EnCana Senlac piloted the solvent-aided process (SAP), where butane was injected with steam.…”
Section: Solvent Enhanced Sagd Processmentioning
confidence: 99%
“…They concluded that smaller solvent slugs are more effective in bitumen recovery and that there is an optimum combination of solvent and steam slug size. These earlier efforts to improve steamflood process with the use of solvent led some investigators to suggest the combination of thermal effect and solvent dilution in SAGD (9,10) . Gupta et al (11) at EnCana Senlac piloted the solvent-aided process (SAP), where butane was injected with steam.…”
Section: Solvent Enhanced Sagd Processmentioning
confidence: 99%
“…These earlier efforts to improve steam flood process with the use of solvent led some investigators to suggest the combination of thermal effect and solvent dilution in SAGD (Palmgren and Edmunds 1995;Butler and Yee 2000). Gupta et al (Gupta, Gittins et al 2002), at EnCana Senlac, piloted the solvent aided process (SAP), where butane was injected with steam.…”
Section: Solvent Co-injectionmentioning
confidence: 99%
“…All rates were scaled to represent a horizontal well length of 700 metres. Since the 0.5-metre model took a prohibitively long amount of time to run (over 100 hours) and the 2-metre model gave unacceptable results (1-minute run time) the decision to use 1-metre grid blocks (1-hour run time) was confirmed (7) .…”
Section: Grid Block Size Sensitivitymentioning
confidence: 99%